PERANCANGAN SISTEM JARINGAN KOMPUTER DENGAN MULTI-ISP MENGGUNAKAN METODE PCC, MANAJEMEN BANDWIDTH, DAN WIRELESS TERPUSAT PADA SMKN 4 KOTA TASIKMALAYA - Rifan Fauzi Rohandi; selly auliya; Helmy Dzulfikar (Universitas Dharmawangsa, 2026)
This study aims to design a computer network system that improves stability, efficiency, and equal distribution of internet access in SMKN 4 Tasikmalaya, which has a high number of users. The main problems identified include suboptimal utilization of multiple Internet Service Providers (multi-ISP), uneven bandwidth management, and the absence of a centralized wireless system. This research adopts a quantitative approach using the Network Development Life Cycle (NDLC) method, which consists of analysis, design, and simulation stages. The proposed design applies load balancing using the Per Connection Classifier (PCC) method, bandwidth management using Per Connection Queue (PCQ), and centralized wireless control using CAPsMAN. The result of this study is an integrated network system design capable of distributing traffic evenly, improving bandwidth efficiency, and supporting user mobility through a single SSID. This study is expected to provide a solution for improving network service quality in educational environments with high user density.